Improving Science Education Students' Argumentation Skills Through a Moodle LMS-Based Research Methods Course - Gunawan Gunawan; Agus Abhi Purwoko; Agus Ramdani (Indonesian, 2022)
Improving postgraduate students' argumentation skills requires innovative learning environment stimulation through the utilization of technology such as a Learning Management System (LMS). This study aims to develop and test the effectiveness of a Moodle-based LMS in improving the argumentation skills of Master of Science Education students at the University of Mataram in a Research Methods course. The method used is Research and Development (R&D) with the ADDIE model, where the implementation phase employed a one-group pretest-posttest experimental design involving 18 postgraduate students. Argumentation skills data were collected through written test instruments based on Toulmin's framework (claim, data, warrant, backing), which were further deepened through intensive interviews. The results showed that the developed Moodle-based LMS was categorized as highly valid, with an average validator score of 4.05. The use of this platform was proven to significantly and effectively improve students' argumentation skills. Based on the indicator analysis, the highest average score was achieved in the warrant aspect (82.68), followed by backing (82.02) and claim (81.94), while the data aspect (81.78) obtained the lowest score. In conclusion, the Moodle-based LMS for research methodology course materials is valid and effective in optimizing the argumentation skills of Master of Science Education students.